1981
DOI: 10.1128/jb.146.1.10-17.1981
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of maltose transport in malB mutants of Escherichia coli through calcium-induced disruptions of the outer membrane

Abstract: The barrier function of the Escherichia coli outer membrane against low concentrations of maltose in strains missing the lambda receptor was partially overcome by treating the cells for 3 h with 25 mM Ca2+. Kinetic analysis of maltose-transport revealed a Ca2+-induced shift of the apparent Km of the system from about 100 microM in cells pretreated with Tris to about 15 microM in cells pretreated with Tris plus Ca2+. In contrast to maltose transport in untreated cells, that of Ca2+-treated lamB cells was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The present experiments extend the application of the reconstitution procedure with calcium-permeabilized cells (5,6) in one significant way. Until now, proteins introduced into the periplasm by this technique have always been rather acidic, and hence negatively charged at the pH (7.0) used for reconstitution (6).…”
Section: Discussionmentioning
confidence: 54%
“…The present experiments extend the application of the reconstitution procedure with calcium-permeabilized cells (5,6) in one significant way. Until now, proteins introduced into the periplasm by this technique have always been rather acidic, and hence negatively charged at the pH (7.0) used for reconstitution (6).…”
Section: Discussionmentioning
confidence: 54%
“…In the present paper we investigated whether the Ca21induced uptake of protein into the periplasm (4,5) is mechanistically related to the CaU-induced uptake of DNA during transformation (23). Using an E. coli strain containing a nonpolar deletion in malE, we compared the conditions required for transformation by plasmid DNA with the conditions necessary for reconstitution of maltose transport by exogenous MBP (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that Ca2+ treatment of E. coli and Salmoniell(l tvyphimurium at a low temperature induces a reversible permeabilization of the outer membrane of these organisms. This phenomenon allows efficient reconstitution of transport and chemotaxis in binding-protein-deficient mutants after import of exogenous binding protein into the periplasm (4)(5)(6). Under optimal conditions, about 20% of the cells were fully competent for uptake of proteins into the periplasm.…”
mentioning
confidence: 99%
“…We show here that maltose chemotaxis in E. coli can be reconstituted by the addition of exogenous MBP to strains lacking this protein. The procedure, based on Ca2+-induced permeabilization of the outer membrane of gram-negative bacteria (10), was used previously to reconstitute transport in mutants lacking binding proteins (11). Hazelbauer and Adler (22) reported that galactose chemotaxis could be restored to osmotically shocked cells of wild-type strains by adding shock fluid containing GBP to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently developed a technique whereby soluble substrate-binding proteins can be introduced into the periplasmic space after Ca2+induced permeabilization of the outer membrane of gramnegative bacteria. Import and function of these proteins can be demonstrated by the reconstitution of transport in mutants lacking binding protein (10,11).…”
mentioning
confidence: 99%